Novel missense mutation in the NOD2 gene in a patient with early onset ulcerative colitis: causal or chance association? - Girardelli, Martina; Vuch, Josef; Tommasini, Alberto; Crovella, Sergio; Bianco, Anna Monica (Int J Mol Sci, 2014)
Deregulated immune response to gut microflora in genetically predisposed individuals is typical for inflammatory bowel diseases. It is reasonable to assume that genetic association with the disease will be more pronounced in subjects with early onset than adult onset. The nucleotide-binding oligomerization domain containing-2 gene, commonly involved in multifactorial risk of Crohn's disease, and interleukin 10 receptor genes, associated with rare forms of early onset inflammatory bowel diseases, were sequenced in an early onset patient. We identified a novel variant in the NOD2 gene (c.2857A > G p.K953E) and two already described missense variants in the IL10RA gene (S159G and G351R). The new NOD2 missense variant was examined in silico with two online bioinformatics tools to predict the potentially deleterious effects of the mutation. Although cumulative effect of these variations in the early onset of the disease can be only hypothesized, we demonstrated that family information and in silico studies can be used to predict association with the disease.
Keywords: Age of Onset; Amino Acid Sequence; Base Sequence; Child; Colitis, Ulcerative; Crohn Disease; DNA Mutational Analysis; Genetic Predisposition to Disease; Genotype; Humans; Interleukin-10 Receptor alpha Subunit; Interleukin-10 Receptor beta Subunit; Molecular Sequence Data; Mutation, Missense; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Risk Factors; Sequence Homology, Amino Acid